2017
DOI: 10.1021/acssuschemeng.7b00604
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transition Metal Oxide Catalysts on MEA Solvent Regeneration for the Post-Combustion Carbon Capture Process

Abstract: Large heat duty for amine regeneration in absorptionbased CO 2 capture is one of the major drawbacks of this process. Along with a highly endothermic carbamate breakdown reaction in the stripper, the difficulty of proton transfer from protonated amines to water in the amine regeneration process is also considered a basic reason for high heat duty. Transition metal oxide catalysts can play a vital role in decreasing the required thermal energy for amine regeneration in the stripper by providing Bronsted acids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 29 publications
(36 reference statements)
2
88
0
Order By: Relevance
“…Silica gel with similar particle size and porosity to TiO(OH) 2 barely changes the CO 2 sorption breakthrough profile. Qualitatively consistent with the Bhatti et al work 15 , TiO 2 also barely changes the CO 2 sorption breakthrough curve. Also, recently reported H-ZSM5 13,14 does not change CO 2 breakthrough curve much.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Silica gel with similar particle size and porosity to TiO(OH) 2 barely changes the CO 2 sorption breakthrough profile. Qualitatively consistent with the Bhatti et al work 15 , TiO 2 also barely changes the CO 2 sorption breakthrough curve. Also, recently reported H-ZSM5 13,14 does not change CO 2 breakthrough curve much.…”
Section: Resultssupporting
confidence: 89%
“…Idem et al reported that H-ZSM and γ-Al 2 O 3 could be used to accelerate the amine based solvent regeneration and thus reducing the heat duty for amine regeneration 13,14 . Bhatti et al 15 recently reported an inspiring finding that transition metal oxides could affect spent monoethanolamine (MEA) regeneration. Two of those materials, MoO 3 and V 2 O 5 , were found to improve desorption rates substantially because, in fact, they react and dissolve in the CO 2 -rich MEA solvent.…”
Section: Introductionmentioning
confidence: 99%
“…There are several techniques for post combustion CO2 capture such as absorption, adsorption, membrane, and cryogenics [5]- [7]. Absorption technique using aqueous amine, for instance monoethanolamine (MEA), diethanolamine (DEA), and piperazine [8]- [10] has been employed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of both solid bases onto a tertiary amine have rarely been discussed either. The effects of solid acid catalysts (γ-Al 2 O 3 , H-ZSM-5, TiO(OH) 2 , and transition metal oxides V 2 O 5 , MoO 3 , WO 3 , TiO 2 , and Cr 2 O 3 ) to MEA [9,21,22,23,24,25] and DEA [26] have also been studied and proven to be effective in the reduction of heat duty. Some studies have been completed to investigate the effects of solid acid catalysts (H-ZSM-5, MCM-41 and SO 4 2− /ZrO 2 ) with blended amine solvents of 5 + 1.0 mol/L MEA-DEEA and MEA-1DMA-2P [9].…”
Section: Introductionmentioning
confidence: 99%